Tertiarization and spatial configuration in Mexico - Carrillo Arteaga, Brian Eric; Cadena Vargas, Edel (Acta Universitaria, 2019)
The process of tertiarization and the degree to which it prevails over the spatial configuration of the territory need to be observed considerably. In this sense, through the Economic Specialization Index and triangular coordinate diagrams, applied to the gross census added value, the process of tertiarization in Mexico is explored by metropolitan area, identifying in turn the most relevant metropolitan area of the process. Subsequently, through the cluster analysis technique and the atypical value (Anselin Local Moran's I), the 12 tertiary sectors of the Industrial Classification System of North America (ICSNA) are spatially examined, using the delimitation by electoral section, its census statistics and the National Statistical Directory of Economic Units of Mexico (NSDEU), to identify the spatial distribution of the main urban agglomerations and the type of urban segregation. Therefore, it is possible to glimpse the practical field of the research carried out and the advantages of the exposed analysis model.